The latency of evoked otoacoustic emissions: its relation to hearing loss and auditory evoked potentials - Hoth, Sebastian; Weber, Frank Nicolas (Scandinavian audiology, 2001)
The latencies of transient evoked otoacoustic emissions (TEOAE), distortion product otoacoustic emissions (DPOAE) and auditory brainstem responses (ABR) have been studied in 173 patients with cochlear hearing impairment. No systematic or significant correlation between the OAE latency and the hearing loss at the corresponding frequency could be found, whereas the ABR latencies increase by a small but significant amount with increasing hearing loss. This can be explained by a broadening of the excited area and its shifting towards a more apical position if the hair cell population in the basal turn is depleted. Because of the considerable intersubject variability of OAE latencies the data do not allow to decide whether they are not influenced by cochlear hearing loss or whether an effect is merely not observable. The large variability is attributed to the interindividual differences of OAE generation time and return delay whereas the travel time of the primary wave is less variable as can be seen from the low variability of ABR latencies.